Humanist Learning With Multiple Intelligences Strategy On Religious Education - Imron Rosady (FALASIFA : Jurnal Studi Keislaman, 2022)
Learning in Islamic education is very important in the application of learning with multiple intelligences in Islamic Religious education learning. The learning planning document is called a lesson plan, there is multiple intelligences research at the time of acceptance of new students to find out their intelligence, students are grouped based on their respective intelligence. The implementation of multiple intelligences in Islamic religious education learning in schools has been carried out well. The lesson plan has been owned by the religious education teacher before the lesson is carried out. The main basis for teachers in making lesson plans for religious education learning is the linguistic intelligence of students by adjusting all learning activity plans with linguistic intelligence indicators. The implementation of the multiple intelligences linguistics strategies in religious education learning has been carried out with learning activities that are adapted to the linguistic intelligence of students, both activities at the beginning of learning such as apperception, warner, and scene setting, core activities are presented with methods that are following linguistic intelligence, and activities at the end of the lesson.